Presidential Inauguration: Pertanggungjawaban Presiden Indonesia Dalam Prosedur dan Materi Sumpah Jabatan - Winda Sari,; Fitra Arsil,; Nurul Insi Syahruddin,; Desi Fitriyani, (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2023)
This article examines the validity and accountability of Indonesian’s President based on the procedures and content of the office’s oath. The research method used is doctrinal, with a legislative approach and a constitutional comparison of fifty countries in the world that adhere to the presidential system of government. The results shows normatively, the authority to inaugurate the president is given to the People's Consultative Assembly (MPR) based on Article 9 of the 1945 Constitution. However, in practice, MPR doesn’t inaugurate the president because it only witnesses the president reciting the oath. Nevertheless, the practice of inauguration is still valid. A comparison of fifty countries shows a trend of the president taking the oath before parliament with the alternative of taking the oath before the Supreme Court (MA) if the MPR is absent. This trend is also applied in Indonesia, but ideally swearing before the Supreme Court is no longer relevant in Indonesia. Seeing the coherence and logical consequences of the president's relationship in formal accountability is closer to the Constitutional Court, in this case as a priveligiatum forum for impeachment events. Thus, the procedure for swearing in the president is more appropriate in front of the MPR, witnessed by the Chairperson of the Constitutional Court. For the oath content , although it is not explicitly stated to whom, the moral responsibility of the president is still addressed to the people as the mandate giver.